2003
DOI: 10.1152/ajplung.00426.2002
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid effects on vitamin K-dependent carboxylase activity and matrix Gla protein expression in rat lung

Abstract: The role of glucocorticoids in the regulation of vitamin K-dependent carboxylase activity was investigated in fetal and adult lung. Glucocorticoid deficiency induced by adrenalectomy (ADX) stimulated adult lung growth and reduced carboxylation in a tissue-specific manner. Type II epithelial cells were enriched in carboxylase activity, where ADX-induced downregulation was retained in freshly isolated cells. Carboxylase activity in fetal type II cells was one-half that found in fetal fibroblasts isolated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…MGP is one of the noncollagenous bone matrix proteins. In addition to our findings, GC-dependent MGP upregulation has also been reported in rat lung cells [30]. A previous study of MGP knockout mice suggests that MGP is an inhibitor of bone mineralization, as MGP-deficient mice exhibit inappropriate calcification of various cartilages and ectopic vascular calcification [20].…”
Section: Discussionsupporting
confidence: 88%
“…MGP is one of the noncollagenous bone matrix proteins. In addition to our findings, GC-dependent MGP upregulation has also been reported in rat lung cells [30]. A previous study of MGP knockout mice suggests that MGP is an inhibitor of bone mineralization, as MGP-deficient mice exhibit inappropriate calcification of various cartilages and ectopic vascular calcification [20].…”
Section: Discussionsupporting
confidence: 88%
“…This mimics observations in humans treated with glucocorticoids (52). It has also been reported that both the vitamin K-dependent carboxylase activity and the biosynthesis of its substrates are enhanced by glucocorticoids (53,54). This was not seen in Tg mice, in which glucocorticoid signaling was disrupted in osteoblasts.…”
Section: Figure 13supporting
confidence: 83%
“…This model provides an ideal system in which to examine specific regulators of lung growth and differentiation by using reagentaddition protocols. Increased MGP mRNA expression over the culture interval mimics the early embryonic in vivo time course (17). A stereotypic morphological pattern of explant growth was observed in control cultures, characterized by a high degree of distal epithelial branching (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Total RNA (0.1-1 g) was reverse-transcribed for 1 h at 42°C by using poly(dT) primers, 500 M deoxynucleotides, 10 mM dithiothreitol, 1ϫ RT buffer, and an RNase H Ϫ reverse transcriptase (Superscript H Ϫ ; Invitrogen) in a total volume of 20 l. After RT, samples were variably diluted for subsequent PCR amplification; dilutions were empirically based on relative abundance of the respective gene product in fetal lung. MGP mRNA expression was quantified by competitive PCR, as described previously (17). Both endogenous MGP and an MGP cDNA mimic amplified with equal efficiency by using the same set of primers that included forward primer 5Ј-CGGAGAAATGCCAACACCTT-3Ј and reverse primer 5Ј-GCAACGAACAATCTGTG-3Ј.…”
Section: Methodsmentioning
confidence: 99%